Gut Microbiota Participates in Antithyroid Drug Induced Liver Injury Through the Lipopolysaccharide Related Signaling Pathway - Sun, Jiayu; Zhao, Fuya; Lin, Baiqiang; Feng, Jing; Wu, Xin; Liu, Yang; Zhao, Lei; Zhu, Biqiang; Wei, Yunwei (Frontiers in Pharmacology, 2020)
Background: Drugs can alter the gut microbiota structure, and gut microbiota dysbiosis in turn is correlated with drug side effects through the intestinal endotoxemia hypothesis. Whether antithyroid drugs (including methimazole and propylthiouracil) cause gut microbiota dysbiosis and whether the gut microbiota is correlated with antithyroid drugs induced liver injury is unknown. Methods: Initial Graves’ disease patients were randomly divided into the methimazole group (n=20) and the propylthiouracil group (n=20) and were followed up every two weeks; 50 healthy controls were also included. The structure and function of gut microbiota were compared from the cross sectional and longitudinal levels. The correlation between the gut microbiota and clinical parameters was also determined. In addition, Sprague-Dawley rats were randomly allotted into 6 groups, including four drug groups, which received daily doses of methimazole (1.5 mg/kg/day; 2.5 mg/kg/day) or propylthiouracil (7.5 mg/kg/day; 12.5 mg/kg/day) by oral gavage, and two control groups received the vehicle. In addition to the indexes mentioned above, intestinal barrier-related indexes were also performed. Results: Results from both clinical trials and animal studies indicate that use or nonuse of drugs, different drugs, different doses and different time points all altered gut microbiota structure; and the liver function related indexes all increased which correlated with gut microbiota. In addition, lipopolysaccharide-related pathways and the lipopolysaccharide concentration in feces and serum all increased after antithyroid drugs administration. These results consistent with the destroyed intestinal barrier in animal study after antithyroid drugs administration. Conclusions: We verified that antithyroid drugs could cause gut microbiota dysbiosis and that the gut microbiota may in turn be correlated with antithyroid drugs-induced liver injury through the intestinal endotoxemia hypothesis.